Al di là dell’opposizione tra “malessere concettuale” e “cattiva coscienza”. Sul disagio dell’antropologia contemporanea di fronte al maltrattamento degli animali - Mancuso, Alessandro (Antropologia Pubblica, 2024)
In this paper I propose a critical examination of the ways in which the intersections between violence, suffering and domination in some of the main new directions of the anthropological study of the relationships between humans and other animals, notably Ingold's approach, Descola’s theory of “schemas of the practice”, and multispecies ethnography. Apparently, and despite the emphasis given to the sentience and forms of agency of non-human animals, as well as to their being active co-participants, together with humans, in the construction of social networks and the habitats that bind both, these intersections do not occupy a prominent place in these approaches, both from the point of view of their theoretical framework and from that of the ethnographic descriptions.The elusive place that the intersections between violence, suffering and domination occupies in contemporary approaches to humans/ other animals relationships has an important consequence in the the lack of a mutually constructive confrontation with animal advocacy’s movements and with the ethical and political theories to which these movements are inspired.It seems desirable and urgent to consider today the issues of suffering and violence inflicted on non-human animals assuming a careful listening posture at positions other than one’s own. Such pluralism, to be adopted both on the level of scientific debate and on that of dialogue between different ethical options, is pointed to by some important proposals developed both in other fields of contemporary anthropology and in the reflection on future prospects for the development of an “ecological justice”.